Qualimetric model of the adaptive system of training masters specializing in management of education institutions - Yeromenko, O. (Problems of Engineer-Pedagogical Education, 2021)
The article is devoted to the development of special tools for the implementation of education monitoring – a factor-criterion model that can assess quality using conditional scores. The emphasis is placed on the need to use a qualimetric approach, which makes it possible to standardize the evaluation procedure of a fundamentally new adaptive system of master's degree training, to track the dynamics of its changes and the real state of master's degree training. The paper considers the quality of the adaptive system of training masters specializing in management of education institutions as a set of three components such as the quality of conditions for training masters specializing in management of education institutions at a higher education institution; the quality of implementation of the key training processes; the quality of the training outcomes. These components of the adaptive system of training masters specializing in school management are selected as factors of the corresponding qualimetric model. Each factor is decomposed by defining partial goals and objectives and formulated criteria. The degree of manifestation of the criteria is determined by the expert assessment by competent specialists (teachers, experts, administrators). To objectify the data, an index estimate can be used, which calculates the degree of manifestation using questionnaires, tests, sociometric measures as a fraction of the whole. To agree on the priorities of the participants in the educational process, qualimetric models are supplemented by the importance of factors and criteria. The obtained results of the proposed factor-criterion model will allow identifying weaknesses of the adaptive system, comparing and making the average data from different areas of activity as well as tracking reserves for improving the effectiveness of the adaptive system of training masters specializing in school management. The paper emphasizes the expediency of using the developed model in higher education institutions to carry out incoming and outgoing control to determine changes in the development of educational activities of undergraduates and professional activities of teaching staff for further directions of masters’ degree training within the adaptive system